La crítica de Platón a los matemáticos que toman las hipótesis por principios (República VI-VII).: Una interpretación a la luz de la metáfora del sueño - Pinotti, Graciela Marcos (PLATO JOURNAL, 2020)
In this paper I try to shed light on platonic criticism of mathematicians for taking hypotheses as principles. The mathematician is forced to resort to hypotheses and go beyond the sensible, but he does, according to Plato, ignoring his own abilities. In this sense, his attitude is similar to that of the majority, lover of opinions, unaware that only thanks to the help of thought is it possible to identify what is offered to the senses. This interpretation fits the dream metaphor, which Plato uses to describe both the attitude of the mathematician and that of the majority.